The Effect Of Vegetable Reception Development On Acceptance Of Patients’ Ordinary Food - AASP Chandradewi; Luh Suranadi; Reni Sofiyatin; Indri Aprillia (Poltekkes Kemenkes Mataram, 2023)
Background: The challenge of providing food in the hospital that must be followed up immediately is that there are still many leftovers from the patient's nutrition. The remaining food needs to be paid attention to because the food the patient consumes will help meet energy and nutritional needs. The remaining food is still a lot of vegetables; poor vegetable processing due to the long cooking process will reduce the nutritional content of the vegetables. Processing vegetables is not only to get healthy and nutritious vegetables, but also in the processing, it is expected to produce vegetables that taste delicious and can be consumed by many people, meaning that in processing, you must also think about the acceptance of these foods.Research Methods: To determine the effect of developing vegetable recipes on the acceptability of patients' average food at Dompu Hospital. This study was a quasi-experimental study using a one-group pretest-posttest design. This study was conducted in May 2021. The population of this study was Class III patients, with a sample of 27 patients data analysis using an independent t-test. Research Result: The results showed that the most vegetable residue was scrambled vegetables, as much as 88.9%, while the least remaining vegetables, and corn cream soup, as much as 70.3%. The results of the statistical test conducted indicated that there was a significant difference in acceptance after modification of the vegetable recipe (p <0.05). Conclusion: The results of the modification stated that out of 27 samples, eight samples (29.7%) still left vegetables included in the category of many > 20%, and 19 samples (70.3%) used up vegetables so that they were included in the category of less <20%. The comparison of leftover vegetables before and after modification showed that the highest yield was found in scrambled vegetables, as much as 88.9%. In contrast, the fewest remaining vegetables were cream corn soup, as much as 70.3%.